The Mycobacterium tuberculosis specific antigen MPT64 in BALF has potential diagnostic value in the diagnosis of pulmonary tuberculosis - Sun, Jie; Lin, Weiwei; Fang, Shiyu; Jiang, Jinxiong; Liu, Fengjun (Frontiers in Medicine, 2026)
BackgroundRecent research on the use of the MPT64 antigen of Mycobacterium tuberculosis (MTB) in tuberculosis diagnosis has intensified. However, its detection in bronchoalveolar lavage fluid (BALF) has not been previously documented. This study aims to fill that gap.MethodsWe included a total of 176 patients, divided into a pulmonary tuberculosis (PTB) group of 104 cases and a non-tuberculosis (Non-TB) group of 72 cases as the control group. The PTB group includes 59 with bacteriologically confirmed PTB (BC-PTB) and 45 with clinically diagnosed PTB with negative pathogens (CD-PTB). The concentrations of MPT64 antigens were detected by enzyme-linked immunosorbent assay (ELISA). Optimal cut-off values were determined by receiver operating characteristic (ROC) curves to evaluate antigen diagnostic capability for active PTB, compared with acid-fast bacilli (AFB) and Xpert MTB/RIF.ResultsXpert MTB/RIF Ct values and MPT64 concentration show significant negative correlation (R = -0.719, P < 0.0001), AFB and MPT64 concentration show significant positive correlation (R = 0.777, P < 0.0001). MPT64 showed a sensitivity of 59.62% (95% CI: 50.01–68.54%) in 104 cases, significantly higher than AFB (26.92%, P < 0.001) and slightly higher than Xpert MTB/RIF (56.73%, P = 0.673). Its specificity was 88.89% (95% CI: 79.58–94.26%), lower than both AFB and Xpert MTB/RIF (100%, P = 0.006). Sensitivities for BC-PTB and CD-PTB were 64.41% (95% CI: 51.66–75.40%) and 53.33% (95% CI: 39.08–67.06%), respectively, P = 0.314.ConclusionThe use of ELISA to detect the MPT64 in BALF may serve as an important supplementary diagnostic method for pulmonary tuberculosis, particularly for bacterial-negative pulmonary tuberculosis.